Application of Nano-Delivery Systems in Lymph Nodes for Tumor Immunotherapy - Xia, Yiming; Fu, Shunli; Ma, Qingping; Liu, Yongjun; Zhang, Na (Nano-Micro Letters, 2023)
Immunotherapy has become a promising research “hotspot” in cancer treatment. “Soldier” immune cells are not uniform throughout the body; they accumulate mostly in the immune organs such as the spleen and lymph nodes (LNs), etc. The unique structure of LNs provides the microenvironment suitable for the survival, activation, and proliferation of multiple types of immune cells. LNs play an important role in both the initiation of adaptive immunity and the generation of durable anti-tumor responses. Antigens taken up by antigen-presenting cells in peripheral tissues need to migrate with lymphatic fluid to LNs to activate the lymphocytes therein. Meanwhile, the accumulation and retaining of many immune functional compounds in LNs enhance their efficacy significantly. Therefore, LNs have become a key target for tumor immunotherapy. Unfortunately, the nonspecific distribution of the immune drugs in vivo greatly limits the activation and proliferation of immune cells, which leads to unsatisfactory anti-tumor effects. The efficient nano-delivery system to LNs is an effective strategy to maximize the efficacy of immune drugs. Nano-delivery systems have shown beneficial in improving biodistribution and enhancing accumulation in lymphoid tissues, exhibiting powerful and promising prospects for achieving effective delivery to LNs. Herein, the physiological structure and the delivery barriers of LNs were summarized and the factors affecting LNs accumulation were discussed thoroughly. Moreover, developments in nano-delivery systems were reviewed and the transformation prospects of LNs targeting nanocarriers were summarized and discussed. Highlights: 1 The physiological structure and the drug delivery barriers of lymph nodes were described. 2 The factors affecting lymph nodes accumulation in nano-delivery systems were discussed. 3 The recent progress of nano-delivery carriers applied for lymph nodes immunotherapy was further categorized and reviewed.